An overview of the pressure- and strain-induced changes in the structural and optoelectronic properties of organometal halide perovskites. (June 2022) - Attique, Sanam; Ali, Nasir; Imran, Tahir; Rauf, Sajid; Khesro, Amir; Ali, Shahid; Wang, Weijian; Khatoon, Rabia; Abbas, Akmal; Ullah khan, Ehsan; Yang, Shikuan; Wu, Huizhen
Abstract: Organometal halide perovskites (PVKs) have demonstrated their potential in photovoltaics in terms of higher photovoltaic efficiency, aiming to achieve the Shockly-Quieser limit of a single-junction solar cell. Understanding the photo-optical and structural properties of PVKs is crucial to further improving their photovoltaic efficiency. Defects-free PVKs with a suitable energy bandgap (EBG  ∼ 1.34 eV) are desirable to capture most of the solar radiations; however, the EBG of the state-of-the-art PVKs is not the ideal one. Compositional engineering offers EBG tunability but decreases carrier lifetime and increases material instability. The application of hydrostatic pressure is a green route, which initiates structural changes in the PVKs and tunes their EBG, leading to the emergence of interesting material properties, including piezochromism, metallization, photoresponsivity, and structural stability. Therefore, understanding the interplay between pressure-induced electronic and structural changes is crucial. Herein, the pressure-induced modifications in structural and optoelectronic properties are elaborated. Particularly, pressure-induced properties in single crystals, lower-dimensional PVKs, and all-inorganic PVKs are comprehended. Moreover, PVK amorphization and strain-induced properties of various PVK materials are also summarized. The review is concluded with an outlook discussing the challenges associated with the pressure induction on PVK material and our perspective to resolve these issues and future work.